Cardiotoxic Effects of Yew Tree and Pink Periwinkle Alkaloids - G. S. Mal; E. B. Artyushkova; M. P. Gladchenko; A. A. Ivanova (Безопасность и риск фармакотерапии, 2021)
Antitumour herbal medicines based on pink periwinkle and yew tree alkaloids are included in combination therapies for many types of cancer. The use of these classes of products may entail cardiotoxic effects leading to life-threatening conditions. The aim of the study was to analyse scientific literature on cardiotoxic effects of anticancer drugs based on yew tree alkaloids (taxanes) and pink periwinkle alkaloids (vinca alkaloids). The results of the analysis demonstrated that the main manifestations of taxane-induced cardiotoxicity were bradycardia, atrioventricular block, atrial and ventricular arrhythmias. Concomitant use of taxanes and anthracycline antibiotics exacerbated cardiotoxic effects of both drug classes. The use of vinca alkaloids was associated with haematological toxicity in the form of neutropenia, while cardiotoxic effect was rarely observed during monotherapy. Raising awareness among oncologists, cardiologists, and other specialists involved in the management of cancer patients about potential cardiac complications of antitumour therapy contributes to early detection of adverse reactions and allows for individual correction of treatment regimens, especially in patients with predisposition to cardiovascular disease.